Discussion on several problems in the construction of joint drilling geological section surveys - Weimin He (地球与行星物理论评)
Based on "Surveying and prospecting of active fault GB/T36072-2018", "Active fault survey—drilling DB/T 92-2022" and other current standards, the basic requirements and main problems in the construction of joint drilling geological section surveys across hidden active faults are discussed. The current technical standard has the following problems: (1) the requirement of core recovery rate is low; and (2) low requirements for drilling depth and distance between boreholes across the hidden reverse fault. The following improvement measures are put forward: (1) the core recovery rate of all kinds of rock and soil should be greater than the value required by the current technical standards and the core recovery rate of clay should not be less than 99%; (2) the drilling across the hidden reverse fault should be deeper than the depth required by the current technical standards; when the thickness of the Quaternary system is thin, the drilling located in the hanging wall of the reverse fault near the uppermost point should continue to drill after drilling into the pre-Quaternary system in the hanging wall, and the drilling should reach the depth that can expose the pre-Quaternary system in the footwall; (3) when the fault displacement of the hidden reverse fault in the Quaternary system is small, the distance between the two adjacent boreholes on both sides of the uppermost point of the reverse fault needs to be 1-3 m or even smaller. The drilling layout method and the method of determining the occurrence of hidden faults in the joint drilling geological section surveys are added. Some uncertain factors in fault identification of joint drilling geological section surveys are analyzed, and corresponding countermeasures are proposed. It is also pointed out that the construction of joint drilling geological section survey is an information construction based on dynamic design, and the on-site technical director and their construction site technical management play an important role in the joint drilling geological section surveys.